Depletion of histone demethylase KDM5B inhibits cell proliferation of hepatocellular carcinoma by regulation of cell cycle checkpoint proteins p15 and p27. Issue 1 (December 2016) - Wang, Dong; Han, Sheng; Peng, Rui; Jiao, Chenyu; Wang, Xing; Yang, Xinxiang; Yang, Renjie; Li, Xiangcheng
Abstract Background KDM5B is a jmjc domain-containing histone demethylase which remove tri-, di-, and monomethyl groups from histone H3 lysine 4 (H3K4). KDM5B has been determined as an oncogene in many malignancies. However, its expression and role in hepatocellular carcinoma (HCC) remain unknown. Methods We detected the expression of KDM5B in HCC tissues and cell lines. Cell proliferation was performed to reveal the role of KDM5B depletion on HCC cells both in vivo and in vitro. Flow cytometry was used to analyze the cell cycle and chip analysis was conducted to determine the direct target of KDM5B. Results KDM5B is frequently up-regulated in HCC specimens compared with adjacent normal tissues and its expression level was significantly correlated with tumor size, TNM stage, and Edmondson grade. Moreover, Kaplan-Meier survival analysis showed that patients with high levels of KDM5B expression had a relatively poor prognosis. Knockdown of KDM5B notably inhibits HCC cell proliferation both in vivo and in vitro via arresting the cell cycle at G1/S phase partly through up-regulation of p15 and p27. Further molecular mechanism study indicates that silencing of KDM5B promotes p15 and p27 expression by increasing histone H3K4 trimethylation in their promoters. Conclusions KDM5B could be a potentially therapeutic target, which provides a rationale for the development of histone demethylase inhibitors as a strategy against HCC.